Berkeley on religious truths: a reply to Keota Fields. Issue 6 (2nd November 2022) - Pearce, Kenneth L.
ABSTRACT: Berkeley admits that certain religious utterances involve words that do not stand for ideas. Nevertheless, he maintains, these utterances may express true beliefs. According to the use theory interpretation of Berkeley, these true beliefs consist in dispositions to follow certain rules. Keota Fields has objected that this interpretation is inconsistent with Berkeley's commitment to the universal truth of the Christian revelation. On Fields' alternative interpretation, the meanings of these utterances are ideas in the mind of God, and we assent to these sentences 'at secondhand', deferring to God for the content of our belief. While Fields' criticisms of the use theory are illuminating, and his alternative proposal is ingenious, neither of them ultimately works. In this paper, I reply to three of Fields' criticisms of the use theory, then press two objections against his alternative proposal. I argue that, although Berkeley is committed to the universal truth of the Christian revelation, this truth is not constituted by ideas in either human or divine minds, but rather by God's universal commands which order the life of the Christian community toward the good.